2004
DOI: 10.1063/1.1634692
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved analysis of the white photoluminescence from SiO2 films after Si and C coimplantation

Abstract: The analysis of the white photoluminescence (PL) from Si+ and C+ coimplanted SiO2 is reported as a function of the implanted dose. By both steady and time-resolved measurements, the presence of several components in the emission between 2 and 3.3 eV has been resolved. The decays of the PL transients are characterized by short lifetimes, below 2 ns. For the emission at 2.1–2.3 eV, photoluminescence decay transients have been measured, obtaining a fast relaxation component of about 50–70 ps, followed by a slower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…A broad white luminescence is interesting in optoelectronic applications, for use in multicolour displays or for illumination purpose. Moreover, C-related bands show a very short lifetime with a value of the order of 50-70 ps, which gives interest to these systems for optoelectronic application where fast switching behaviour is important [12]. In addition to the optical properties previously reported, it appears interesting to study the transport properties in this kind of layers in order to fabricate optoelectronic devices.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A broad white luminescence is interesting in optoelectronic applications, for use in multicolour displays or for illumination purpose. Moreover, C-related bands show a very short lifetime with a value of the order of 50-70 ps, which gives interest to these systems for optoelectronic application where fast switching behaviour is important [12]. In addition to the optical properties previously reported, it appears interesting to study the transport properties in this kind of layers in order to fabricate optoelectronic devices.…”
Section: Introductionmentioning
confidence: 97%
“…The emission energy may vary, depending on one hand on the matrix composition, mostly silicon oxide [7,8], also nitride [9] and oxycarbide [10], on the other hand by the incorporation of other elements in the Si-nc like C [11]. In particular, we have previously shown that the use of alternative nanoparticles with different chemical composition may be a viable method to obtain emission in the visible spectrum, in particular by co-implanting silicon-rich silicon oxide (SRSO) with carbon [11,12]. In this latter case, the processed structures show a white PL consisting in different bands: one in the red-infrared region attributed to the Si-nc, and two other bands, located in the blue or the green, assigned to the formation of SiC compounds or C graphitic-like aggregates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The main obstacle lies in the low light emission efficiency. In recent years, considerable attention has been paid to the light emission from silicon oxycarbide films, the advantages of which include strong light emission and wide tunable optical band gap, making it useful for the design of efficient light emitting devices [16,17]. In addition, silicon oxycarbide is also regarded as a promising host material for rare earth such as Er and Eu [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The decay times are the results of fitting the decaying process (see the inset) with a double exponential decaying function, thus there is a long decay time attribute and a short decay time attribute. Such a fitting procedure has been employed by many researchers [12], to which the tacit assumption is that two decaying paths are responsible for the decaying process. In a model proposed by Calcott et al [13] for porous silicon, it states that the electron -hole exchange interaction splits the excitonic levels by an energy D due to quantum confinement, and the upper level (a triplet state) and the lower level (a singlet state) have different radiative decay rates [14].…”
mentioning
confidence: 99%